In search of Chingis-Khan's Good Light: The Rise in Importance of Chingis-Khan's Image and the Neo-Dastan Discourse in Kazahstan - Xasanov, Batir (Jama'a: an Interdisciplinary Journal of Middle East Studies, 2012)
With the decline in the importance of the image of Lenin in the Soviet Union in the early 1990s, and with the demise of his image in the countries formed after the breakup of the Soviet Union, Chingis-Khan's image began to rise in Central Asia, Mongolia, and certain parts of Russia. That phenomenon is related to a wider discourse, which - for lack of any terminology established in the field - the author terms 'Neo-Dastan discourse'. Though the roots of the proper formative phase occured actually in the late Soviet period (from the late 1950s until the Perestroika years in the late 1980s). Following Stalin's death, in the mid-1950s intellectuals of the indigenous populations in the Eastern regions of the Soviet Union began to challenge the basic assumptions of Soviet historiography. These basic assumptions had often been laid down by Stalin himself, and they were meant to justify the interethnic order in the Soviet Union. Even after more than twenty years since the breakup of the Soviet Union, this discourse has not lost its importance, quite on the contrary - the discourse has spread further, and it has been recruited for present purposes and future aims. One of the main test cases for understanding the formation process of the Neo-Dastan discourse - the changing image of Chingis-Khan - has occurred and is still underway in Kazakhstan today.